Neue Punktionstechniken in der Urologie mittels 3D-gestützter Bildgebung - Ritter, Manuel; Rassweiler-Seyfried, Marie-Claire; Michel, Maurice Stephan (Der Urologe, 2012)
The selective use of various puncture techniques for diagnostic or therapeutic purposes is a component of the daily routine of urologists. The aim of these interventions is always a safe and rapid puncture at the appropriate target point. Nowadays, imaging systems are increasingly being used in urology with the aim to achieve a more precise and safer planning and execution of punctures through an increased accuracy by the use of 3D representation. An approach to the solution to achieve this aim is the fusion of 3D reconstruction by magnetic resonance imaging (MRI) or computed tomography< (CT) with real-time imaging procedures, such as sonography or fluoroscopy.